Determination of hexokinase and other enzymes which possibly phosphorylate fructose in Neurospora crassa - W. Klingmuller; H. G. Truper (Fungal Genetics Reports, 1965)
Determination of hexokinase and other enzymes which possibly phosphorylate fructose in Neurospora crassa